DETERMINAN PENGGELAPAN PAJAK (TAX EVASION) DENGAN RELIGIUSITAS SEBAGAI VARIABEL PEMODERASI - Ulfa Fauzi Jamalallail; Maria Goreti Kentris Indarti (Faculty of Economics and Business, Universitas Warmadewa, 2022)
The purpose of this study was to determine the effect of machiave11ian, 1ove of money, tax sanctions and se1f assessment system on taxpayers' perceptions of tax evasion (tax evasion) with re1igiosity as a moderating variab1e. The popu1ation used in this study were individua1 taxpayers registered at the West Semarang KPP Pratama in 2020 as many as 38,891 individua1 taxpayers. The number of samp1es in this study were 100 individua1 taxpayers. The research method uses mu1tip1e 1inear regression. The resu1ts of the ana1ysis show that machiave11ian inf1uence on the perception of taxpayers regarding tax evasion (tax evasion). 1ove of money affects the perception of taxpayers regarding tax evasion (tax evasion). Tax sanctions have no effect on taxpayers' perceptions of tax evasion. The se1f-assessment system has no effect on taxpayers' perceptions of tax evasion. Re1igiosity is ab1e to moderate the machiave11ian variab1es on the perception of taxpayers regarding tax evasion (tax evasion). Re1igiosity is ab1e to moderate the 1ove o money variab1e on the taxpayer's perception of tax evasion (tax evasion). Re1igiosity is ab1e to moderate between the variab1es of tax sanctions on the perception of taxpayers regarding tax evasion (tax evasion). Re1igiosity is ab1e to moderate the se1f-assessment system variab1e on the taxpayer's perception of tax evasion (tax evasion).